Genus Oncopsis Burmeister (Cicadellidae: Eurymelinae) new to Korea with description of a new species - Hamzah, Munirah; Jung, Sunghoon (Zootaxa, 2026)
The genus Oncopsis Burmeister, 1838 is recorded for the first time from Korea with a new record, Oncopsis wagneri Knight, 1971 and a new species, Oncopsis alpinus sp. nov. Description of species, habitus, and illustration of male genitalia are provided.